"Conservative" Ideological Principles and Social Programs. Issue 2 (June 2017) - Skidmore, Max J.
Abstract : Although Max J. Skidmore employs the form of a review essay in this piece, his analysis is actually not a review, and makes no pretense of reviewing the works listed below. Instead, it is an examination of the failure of what passes today in the United States for conservatism, its inability to achieve the stated goals of its adherents, its role in reducing the ability of those adherents to determine fact from fiction, its harmful effects upon the body politic, its especially harmful effects on social programs, and its revelation of the unanticipated vulnerability of American political institutions.